Geomechanical Basis for Assessing Open-Pit Slope Stability in High-Altitude Gold Mining - Farit Nizametdinov; Rinat Nizametdinov; Denis Akhmatnurov; Nail Zamaliyev; Ravil Mussin; Nikita Ganyukov; Krzysztof Skrzypkowski; Waldemar Korzeniowski; Jerzy Stasica; Zbigniew Rak (Applied Sciences)
The development of mining operations in high-altitude regions is associated with a number of geomechanical challenges caused by increased rock fracturing, adverse climatic conditions, and high seismic activity. These issues are particularly relevant for the exploitation of gold ore deposits, where the stability of open-pit slopes directly affects both safety and extraction efficiency. The aim of this study is to develop and practically substantiate a comprehensive approach to assessing and ensuring slope stability, using the Bozymchak gold ore deposit—located in a high-altitude and seismically active zone—as a case study. The research involves the laboratory testing of rock samples obtained from engineering–geological boreholes, field shear tests on rock prisms, laser scanning of pit slopes, and digital geomechanical modeling. The developed calculation schemes take into account the structural features of the rock mass, geological conditions, and the design contours of the pit. In addition, special bench excavation technologies with pre-shear slotting and automated GeoMoS monitoring are implemented for real-time slope condition tracking. The results of the study make it possible to reliably determine the strength characteristics of the rocks under natural conditions, identify critical zones of potential collapse, and develop recommendations for optimizing slope parameters and mining technologies. The implemented approach ensures the required level of safety.